Towards ab initio structure and response calculations across the nuclear chart - Papakonstantinou, P.; Roth, R.; Hergert, H.; Paar, Ν. (HNPS Advances in Nuclear Physics, 2019)
Starting from the Argonne V18 nucleon-nucleon interaction and using the Unitary Correlation Operator Method, a correlated interaction vucOM has been constructed, which is suitable for calculations within restricted Hilbert spaces. In this work we employ the vucOM in Hartree-Fock, perturbation-theory and RPA calculations. First results are reported on the ground-state properties of various closed-shell nuclei, as well as some excited states. Our results provide valuable information on the properties of the VUCOM and guidance to further optimization. The above scheme offers the prospect of ab initio calculations in nuclei throughout the nuclear chart. It can be used in conjunction with other realistic NN interactions as well, both local and non-local. Various many-body methods can be employed, such as Second RPA, QRPA, Shell Model, etc.